Bioaccessibility of Fukushima‐Accident‐Derived Cs in Soils and the Contribution of Soil Ingestion to Radiation Doses in Children. Issue 7 (30th September 2016) - Takahara, Shogo; Ikegami, Maiko; Yoneda, Minoru; Kondo, Hitoshi; Ishizaki, Azusa; Iijima, Masashi; Shimada, Yoko; Matsui, Yasuto
Abstract : Ingestion of contaminated soil is one potential internal exposure pathway in areas contaminated by the Fukushima Daiichi Nuclear Power Plant accident. Doses from this pathway can be overestimated if the availability of radioactive nuclides in soils for the gastrointestinal tract is not considered. The concept of bioaccessibility has been adopted to evaluate this availability based on in vitro tests. This study evaluated the bioaccessibility of radioactive cesium from soils via the physiologically‐based extraction test (PBET) and the extractability of those via an extraction test with 1 mol/L of hydrochloric acid (HCl). The bioaccessibility obtained in the PBET was 5.3% ± 1%, and the extractability in the tests with HCl was 16% ± 3%. The bioaccessibility was strongly correlated with the extractability. This result indicates the possibility that the extractability in HCl can be used as a good predictor of the bioaccessibility with PBET. In addition, we assessed the doses to children from the ingestion of soil via hand‐to‐mouth activity based on our PBET results using a probabilistic approach considering the spatial distribution of radioactive cesium in Date City in Fukushima Prefecture and the interindividual differences in the surveyed amounts of soil ingestion in Japan. The results of this assessment indicate that even if children were to routinely ingest a large amount of soil with relatively high contamination, the radiation doses from this pathway are negligible compared with doses from external exposure owing to deposited radionuclides in Fukushima Prefecture.